2021
DOI: 10.1177/0192513x211055790
|View full text |Cite
|
Sign up to set email alerts
|

Men in Mixed-Orientation Marriages in Contemporary China: Unpacking the Role of Heteronormativity and Patriarchy

Abstract: This qualitative study based on 34 in-depth interviews (IDIs) with cis-gendered tongzhi (men who are attracted to men) critically explores the factors influencing their decisions to enter mixed-orientation marriages (MOMs) in China. Theoretically, the study weaves together insights from queer and feminist theorizing and analyzes the role of heteronormativity and patriarchy, especially in relation to hegemonic masculine ideals, in the context of marriage norms in contemporary China. Our examination showcases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Furthermore, family shame was a salient factor for bisexual people living in Chinese culture. Research has shown that Chinese bisexual people experience moral oppression and parental expectation to maintain a mixed-gender marriage and have offspring to prevent shaming one’s personal and family’s reputation (Ren et al, 2019; Song et al, 2023). Although the family shame factor may reflect anticipation or reporting of actual familial reactions, Chinese bisexual people can internalize these oppressive messages about family to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, family shame was a salient factor for bisexual people living in Chinese culture. Research has shown that Chinese bisexual people experience moral oppression and parental expectation to maintain a mixed-gender marriage and have offspring to prevent shaming one’s personal and family’s reputation (Ren et al, 2019; Song et al, 2023). Although the family shame factor may reflect anticipation or reporting of actual familial reactions, Chinese bisexual people can internalize these oppressive messages about family to different degrees.…”
Section: Discussionmentioning
confidence: 99%